Acute Myocardial Infarction in Puerperium Stage. A Case Presentation - Teresa Oliva Rivero; Israel Sotolongo Castro; Maria Victoria Jó Díaz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
A 38 year-old hypertensive, smoker female patient was presented. She suferred from an acute myocardial infarction in the mediate puerperium stage of an normal deliver. She was assisted in the Heart intensive care unit taking into consideration the basic care principles for this kind of patient. The infarct was diagnosed due to the clinical picture, and the electrographic alterations as well as the enzimatic alterations. The case is presented because it is a low frequency complication and it is not too much registered in the the medical literature revised.